Library of souls (Miss Peregrine, 3, 1, 2016)
"A boy with extraordinary powers. An army of deadly monsters. An epic battle for the future of peculiardom. The adventure that began with Miss Peregrine's Home for Peculiar Children and continued in Hollow City comes to a thrilling conclusion with Library of Souls. As the story opens, sixteen-year-old Jacob discovers a powerful new ability, and soon he's diving through history to rescue his peculiar companions from a heavily guarded fortress. Accompanying Jacob on his journey are Emma Bloom, a girl with fire at her fingertips, and Addison MacHenry, a dog with a nose for sniffing out lost children. They'll travel from modern-day London to the labyrinthine alleys of Devil's Acre, the most wretched slum in all of Victorian England. It's a place where the fate of peculiar children everywhere will be decided once and for all. Like its predecessors, Library of Souls blends thrilling fantasy with never-before-published vintage photography to create a one-of-a-kind reading experience"--

This dark road to mercy: a novel (HarperLuxe, Harper Collins Publishers, HarperCollins, HarperAudio, William Morrow, an imprint of HarperCollins Publishers, HarperCollins Publishers, 2014)
When their mother dies unexpectedly, twelve-year-old Easter and her six-year-old sister Ruby are shuffled into the foster care system in Gastonia, North Carolina, a town not far from the Appalachian mountains. But just as they settle into their new life, their errant father, Wade, an ex-minor league baseball player whom they haven't seen in years, suddenly appears and wants to spend more time with them. Unfortunately, Wade has signed away legal rights to his daughters, and the only way he can get Easter and Ruby back is to steal them away in the middle of the night. Brady Weller, the girls' court-appointed guardian, begins looking for Wade, and he quickly turns up unsettling information linking Wade to a recent armored car heist, one with a whopping $14.5 million missing. But Brady Weller isn't the only one hunting the desperate father. Robert Pruitt, a shady and mercurial man nursing a years-old vendetta, is also determined to find Wade and claim his due.

After the flood: a novel (HarperCollins, HarperAudio, William Morrow, an imprint of HarperCollinsPublishers, 2019)
A little more than a century from now, our world has been utterly transformed. After years of slowly overtaking the continent, rising floodwaters have obliterated America's great coastal cities and then its heartland, leaving nothing but an archipelago of mountaintop colonies surrounded by a deep expanse of open water. Stubbornly independent Myra and her precocious seven-year-old daughter, Pearl, fish from their small boat, the Bird, visiting dry land only to trade for supplies and information in the few remaining outposts of civilization. For seven years, Myra has grieved the loss of her oldest daughter, Row, who was stolen by her father after a monstrous deluge overtook their home in Nebraska. Then, in a violent confrontation with a stranger, Myra suddenly discovers Row was last seen in a far-off encampment near the Arctic Circle. Throwing aside her usual caution, Myra and Pearl embark on a perilous voyage into the icy northern seas, hoping against hope that Row will still be there. On their journey, Myra and Pearl join forces with a larger ship, and Myra finds herself bonding with her fellow seekers who hope to build a safe haven together in this dangerous new world. But secrets, lust, and betrayals threaten their dream, and after their fortunes take a shocking and bloody turn, Myra can no longer ignore the question of whether saving Row is worth endangering Pearl and her fellow travelers.

Power game (Ghostwalkers, 13, 1, 2017)
"#1 New York Times bestselling author Christine Feehan is "one of the best storytellers around" (RT Book Reviews). Find out why as two lovers surrounded by greed and corruption discover there's no telling whom you can trust--or who will come out on top... When members of a United Nations joint security force are taken hostage by radical terrorists in Indonesia, Captain Ezekiel Fortunes is called to lead the rescue team. Part of a classified government experiment, Zeke is a supersoldier with enhanced abilities. He can see better and run faster than the enemy, disappear when necessary and hunt along any terrain. There are those in the world willing to do anything for power like that... A formidable spy genetically engineered to hide in plain sight, Bellisia rarely meets a man who doesn't want to control her or kill her. But Zeke is different. His gaze, his touch--they awaken feelings inside her that she never thought possible. He's the kind of man she could settle down with--if she can keep him alive.."--